Internal seiches in a karstic mesotrophic lake (Prošće, Plitvice Lakes, Croatia) - Bencetić Klaić, Zvjezdana (Array, 2020)
A lake temperature experiment was performed at the Prošće, Plitvice Lakes, Croatia during a 4-month observational period (6 July–4 November, 2019) to investigate the occurrence and characteristics of internal seiches in the lake. Two-minute mean lake temperatures were measured at a single lake point at fifteen depths ranging from 0.2 to 27 m. Analysis of these data provided insight into the previously unknown and rather complex Prošće Lake seiching. Power spectral densities (PSDs) and magnitude-squared coherences (γ2), together with corresponding cross-spectrum phases that were obtained from the hourly mean lake temperature, air pressure and wind speed data, suggested the presence of three vertical modes of an internal seiche. The first mode (V1H1, period of 6.09 h) corresponds to free baroclinic oscillations; the second mode (V2H1, period of 11.64 h) and the third mode (V3H1, period of 25.60 h) are associated with forced baroclinic oscillations of the lake interior. Excitation of the higher vertical modes is attributed to the influence of dense tributary water. Due to this water influence, vertical temperature gradients in the lake interior were relatively weak; consequently, a single thick metalimnion and/or two metalimnetic layers were established, which resulted in the presence of the V2H1 and V3H1 modes, respectively. Additionally, due to the influence of tributary water, the lake did not attain the typical stratification that is characterized by hypolimnetic temperatures of ≈ 4°C. Instead, during the entire observational period, the hypolimnetic temperatures were consistently above 7.6 °C.